2000
DOI: 10.1177/03635465000280031801
|View full text |Cite
|
Sign up to set email alerts
|

Sex-Related Injury Patterns among Selected High School Sports

Abstract: This cohort observational study was undertaken to test the hypothesis that the incidence of injuries for girls participating in high school sports is greater than that for boys. From 1995 through 1997, players were included in our study if they were listed on the school's varsity team roster for boys' or girls' basketball, boys' or girls' soccer, boys' baseball, or girls' softball. Injuries and opportunities for injury were recorded daily. Certified athletic trainers reported injury and exposure data. Based on… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

20
267
9
8

Year Published

2003
2003
2017
2017

Publication Types

Select...
3
2
2

Relationship

0
7

Authors

Journals

citations
Cited by 335 publications
(304 citation statements)
references
References 10 publications
20
267
9
8
Order By: Relevance
“…A comparison of injury rates from prospective and retrospective research is shown in table 1 and covers high school [14][15][16][17][18][19][20][21], physical education class [22], clubs/sports organizations [23][24][25][26][27], and hospital emergency departments [28,29]. In addition, studies reporting incidence data specifically for knee [18,19,30], ankle [31,32], head [33], and orofacial [34][35][36] injuries are listed. Unfortunately, the injury literature on youth basketball suffers from a broad range of methodological shortcomings, including widely varying definitions of a reportable injury, limited measures of exposure, differing metrics of risk, and poor delineation of the population at risk.…”
Section: Incidence Of Injurymentioning
confidence: 99%
See 3 more Smart Citations
“…A comparison of injury rates from prospective and retrospective research is shown in table 1 and covers high school [14][15][16][17][18][19][20][21], physical education class [22], clubs/sports organizations [23][24][25][26][27], and hospital emergency departments [28,29]. In addition, studies reporting incidence data specifically for knee [18,19,30], ankle [31,32], head [33], and orofacial [34][35][36] injuries are listed. Unfortunately, the injury literature on youth basketball suffers from a broad range of methodological shortcomings, including widely varying definitions of a reportable injury, limited measures of exposure, differing metrics of risk, and poor delineation of the population at risk.…”
Section: Incidence Of Injurymentioning
confidence: 99%
“…Moreover, with the variety of ages in disparate settings (school teams, clubs, physical education classes) across multiple countries, there is little appropriately comparable data. Even the results of the most commonly studied population (American public high school players) vary considerably, from 5.6-36.8 per 100 participants for boys, and 7.8-49 per 100 participants for girls [14][15][16][17]19], although two studies which report injuries per 1,000 hours of participation are similar (3.2-4.0) [17,18]. A coordinated research program with standard protocols is necessary if a clear picture of the level of risk, and associated causal factors, is to emerge.…”
Section: Incidence Of Injurymentioning
confidence: 99%
See 2 more Smart Citations
“…However, the problem that could receive this group-based intervention. Gender differences in sport injury incidence might also affect a program's effectiveness (Powell, & Barber-Foss, 2000;Prodromos et al, 2007), although the program itself is not gender specific and could be delivered to either males or females. Finally, age differences could also affect the outcome, as a result of both age and injury history, and the willingness of older people to receive an hour long intervention session.…”
Section: Discussionmentioning
confidence: 99%